Paternal smoking, genetic polymorphisms in CYP1A1 and childhood leukemia risk - Lee, Kyoung-Mu (2008)
We conducted a case–control study to evaluate the association between paternal smoking and childhood leukemia and to evaluate potential modification by polymorphisms in CYP1A1. Histologically confirmed childhood leukemia cases (n = 164) and non-cancer controls (n = 164) were recruited from three teaching hospitals in Seoul, Korea. Five single nucleotide polymorphisms in CYP1A1 (–17961T>C, –9893G>A, I462V, 1188C>T (*2A), and 11599C>G) were genotyped and haplotypes were estimated by the expectation-maximization method. We also conducted a meta-analysis of 12 studies that have reported the association between paternal smoking and childhood leukemia risk. Paternal smoking at home was associated with all leukemias (OR = 1.8, 95% CI = 1.1–2.8) and acute lymphoblastic leukemia (ALL) (2.0, 1.2–3.4). An increasing trend in risk was observed for pack-years smoked after birth (P(trend) = 0.06 and 0.02, respectively) and the number of smokers in the home during the child's life (P(trend) = 0.05 and 0.03, respectively). Among those without the CGACC haplotype, ALL risk was significantly increased by the father's smoking at home (2.8, 1.5–5.3) and the presence of at least one smoker in the home (2.3, 1.2–4.4), and the test for interaction was significant (P(interaction) = 0.03 and 0.02, respectively). The meta-analysis showed that overall paternal smoking (1.13, 1.04–1.24) and smoking before the pregnancy of the child (1.12, 1.04–1.21) were significantly associated with childhood leukemia risk. Our results suggest that paternal smoking is a risk factor for childhood leukemia and the effect may be modified by CYP1A1 genotype.